Phenoxyalkylimidazoles with an oxadiazole moiety are subject to efflux in Mycobacterium tuberculosis - Thayer, Mai B.; Parish, Tanya (PloS one, 2021)
The phenoxyalkylimidazoles (PAI) are an attractive chemical series with potent anti-tubercular activity targeting Mycobacterium tuberculosis respiration. Our aim was to determine if the PAI compounds are subject to efflux. Two analogs containing an oxadiazole had improved potency in the presence of the efflux inhibitors reserpine and carbonyl cyanide m-chlorophenylhydrazine, whereas the potency of analogs with a diazole was not affected.